2017
DOI: 10.1016/j.envpol.2016.09.052
|View full text |Cite
|
Sign up to set email alerts
|

Arthropod communities in a selenium-contaminated habitat with a focus on ant species

Abstract: The selenium contamination event that occurred at Kesterson Reservoir (Merced Co., CA) during the 1970-80s is a frequently cited example for the negative effects of contamination on wildlife. Despite the importance of arthropods for ecosystem services and functioning, relatively little information is available as to the impacts of pollution on arthropod community dynamics. We conducted surveys of the arthropod community present at Kesterson Reservoir to assess the impacts of selenium contamination on arthropod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Mogren et al (2013) found that levels of arsenic transferred to predators differed based on their feeding strategy, where preying mantids consuming entire arsenic-laden mosquitoes accumulated higher levels than spiders that consumed only internal mosquito body fluids. Species-specific accumulation patterns of heavy metals have also been described for ants residing in the same habitat (Rabitsch, 1997;De La Riva et al, 2017), suggesting possible differences in both metal regulation and diet preferences. Exposure levels may also differ seasonally, depending on the source of the contaminant available in the environment, such as changes in floral nectar availability or herbivore populations.…”
Section: Discussionmentioning
confidence: 92%
“…Mogren et al (2013) found that levels of arsenic transferred to predators differed based on their feeding strategy, where preying mantids consuming entire arsenic-laden mosquitoes accumulated higher levels than spiders that consumed only internal mosquito body fluids. Species-specific accumulation patterns of heavy metals have also been described for ants residing in the same habitat (Rabitsch, 1997;De La Riva et al, 2017), suggesting possible differences in both metal regulation and diet preferences. Exposure levels may also differ seasonally, depending on the source of the contaminant available in the environment, such as changes in floral nectar availability or herbivore populations.…”
Section: Discussionmentioning
confidence: 92%
“…significant differences using the nonparametric Kruskal-Wallis test (Ostertagová et al, 2014;De La Riva et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, to analyse trait patterns between parks, the selected traits were first weighted according to the number of individuals per trap (community weighted mean; Watts & Mason, 2015). Due to the data's non-normality, we then looked for significant differences between parks using the nonparametric Kruskal-Wallis test (Ostertagová et al, 2014;De La Riva et al, 2017).…”
Section: Discussionmentioning
confidence: 99%